2018
DOI: 10.1111/jam.14117
|View full text |Cite
|
Sign up to set email alerts
|

BradyrhizobiumandPseudomonasstrains obtained from coal-mining areas nodulate and promote the growth ofCalopogonium muconoidesplants used in the reclamation of degraded areas

Abstract: Aims: The objective of this work was to isolate and characterize indigenous rhizobia from coal-mining areas able to efficiently nodulate and fix nitrogen in association with Calopogonium mucunoides (calopo). Methods and Results: Isolation, authentication and morphological, biochemical and molecular characterization of the autochthonous rhizobia were performed and their symbiotic efficiency (SE) evaluated. Efficient rhizobial isolates suitable for the inoculation of calopo in coal-mining regions were obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This plant naturally associates with rhizobia, however, stress conditions greatly impact the nodulation process and C . mucunoides plant growth (González et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This plant naturally associates with rhizobia, however, stress conditions greatly impact the nodulation process and C . mucunoides plant growth (González et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Calopogonium mucunoides is a leguminous plant able to grow in acidic soils, thus facilitating the recovery of highly acidic soils associated with coal-mining activities. This plant naturally associates with rhizobia, however, stress conditions greatly impact the nodulation process and C. mucunoides plant growth (González et al, 2019).…”
Section: Maize Plant Growth Promotion Assaymentioning
confidence: 99%
“…For instance, Hu et al [71] suggested that probiotic Pseudomonas communities may manage the functionality of the microbial communities associated with tomato via regulation of important plant-growth-promoting traits. Moreover, some authors have attributed the capacity to form nodules in legumes to some strains of this genus, as well as to some Paenibacillus and Enterobacteria strains [40,[72][73][74]. However, these studies must be taken very cautiously, as they showed no conclusive proof or correct controls.…”
Section: What Are the Nrbes?mentioning
confidence: 99%
“…Plant growth promoting bacteria (PGPB) can act through different mechanisms (direct and indirect) in increasing agricultural productivity, being characterized as an innovative technology for increasing sustainability in agricultural systems (González et al, 2019;Nascimento et al, 2020a). Notoriously, the role played by PGPB in agriculture is consolidated in the provision of nutrients such as nitrogen (N), resulting in the wide use of commercial products used for this purpose (Quintas-Nunes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%